Analisis Supply Chain Risk Management Industri Budidaya Lobster Air Tawar Dengan Pendekatan FMEA - Siti Muhimatul Khoiroh (Universitas Mercu Buana, 2021)
The growing interest of the Indonesian people in the cultivation of LAT (Freshwater Lobster) is one of the effects of government regulation no. 56/ Permen-KP/2016. Since the occurrence of the Covid-19 pandemic with regional restrictions, one of the LAT cultivation industries of the Red Claw (Cherax Quadricarinatus) type in the Sidoarjo area, East Java, has experienced problems in supplying lobster to consumers in various regions outside cities in Indonesia. The delay in the supply of lobster results in delays in the supply of raw materials for consumers, the majority of whom are restaurant or restaurant activists. The success of supply chain management is determined by the number of costs that can be minimized, short time, and quality that is maintained, as well as the level of risk minimization (supply chain risk). Based on the problems that occur, risk identification will be carried out in each process to see its effect on cost, time, and quality. Then proceed with determining the weight based on the level of resistance (severity), possible resistance (occurrence), and the cause of the detected obstacle (detection). The last step is to calculate the RPN (Risk Priority Number) value obtained from the severity results. From the results of the analysis of risk identification and calculation of RPN with the FMEA approach, the highest risk weight with an RPN value of 105 was obtained due to the risk factor for the increase in distribution costs of cultivation products due to the impact of the Covid-19 Pandemic. Thus, the company should consider reorganizing its business strategy to focus on areas that are close to the point of supply of freshwater crayfish.